2006
DOI: 10.1016/j.ejogrb.2005.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of colonisation with group B Streptococci in pregnant women of a multi-ethnic population in The Netherlands

Abstract: Objective: This study was performed to determine the prevalence of GBS and to identify GBS colonisation risk factors in a multicultural population of pregnant women in The Netherlands. We calculated predictive values of cultures in pregnancy for intrapartum GBS carriage. Study design: From a total of 1702 women visiting several antenatal outpatient departments, rectovaginal swabs were collected at 35-37 weeks' gestation. In 761 women swabs were repeated at time of delivery. Carriage of GBS late in third trimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
73
9
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 34 publications
(66 reference statements)
16
73
9
3
Order By: Relevance
“…There was significant relationship between colonization and preterm labor; this inconsistency may be due to the limited number of mothers who participated in the present study and had a history of preterm labor. However, there was no significant relationship between rate of colonization (21%) and age of the mother and preterm labor in Valkenburg-van et al (2006) in Netherlands; these results are consistent with the findings of the present study (Valkenburg-van et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…There was significant relationship between colonization and preterm labor; this inconsistency may be due to the limited number of mothers who participated in the present study and had a history of preterm labor. However, there was no significant relationship between rate of colonization (21%) and age of the mother and preterm labor in Valkenburg-van et al (2006) in Netherlands; these results are consistent with the findings of the present study (Valkenburg-van et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Colonization and subsequent neonatal infection might occur in the womb, at birth, or in the first month of life. The incidence of this infection in first 7 days is referred to as 'premature' and it is called 'delayed' if it happens from the first week up to the first three months after the birth (Valkenburg -van et al, 2006). Additionally, GBS colonization, especially in vagina and rectum, is a common phenomenon among pregnant women and 20-30% of the collected samples from pregnant women with pregnancy age of 35 weeks turn out to be GBS positive (Behrman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, no significant difference was found with regards to parity between GBS colonized and non-colonized. Several studies [27][28][29] found no significant differences in colonization rates by age or parity, while others report associations with young age and lower parity [10,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The different prevalence rates between several studies may be associated with gestational age at culturing, differences in sampling sites (i.e. only vaginal vs. rectovaginal), using different culture techniques, using PCR with different targets, an alteration of prevalence with time, or real differences of prevalence in various populations or ethnic groups (26). In addition, differences in the elapsed time after sampling for transporting clinical specimens to be processed, using different nucleic acid extraction method, as well as using PCR with different targeting can be some reasons for differences related to reported specificity and sensitivity of PCR in several studies.…”
Section: Discussionmentioning
confidence: 99%